Study of recombination process of lead-free cesium titanium (IV) based single halide and mixed halide perovskite compounds absorbing layer. (2021) - Chakraborty, Kunal; Paul, Samrat
Abstract: The present research work represents the study of the recombination process at different positions of a hetero junction solar cell. The study for recombination process at depletion region, quasi-neutral region, front (right) contact region and back (left) contact region for lead-free Cesium Titanium (IV) based single halide perovskites compounds viz Cs2 TiBr6, Cs2 TiI6, Cs2 TiCl6, and Cs2 TiF6 and mixed halide compounds such asCs2 TiI1 Br5, Cs2 TiI2 Br4, Cs2 TiI3 Br3, Cs2 TiI4 Br2, and Cs2 TiI5 Br1 was studied using SCAPS-1D device simulator. The cell architecture used for the study is FTO/TiO2 /absorbing layer/CuSCN/Ag. Open circuit voltage (VOC ) is a key performance parameter to understand the recombination process at the front contact and back contact interfaces of a solar cell device. This research article enumerated the total recombination current density (JTot. Recom ), bulk recombination rate (JBulk ), Schckley-Read-Hall recombination rate or defect recombination rate (JSRH ) for the solar cell device.